METODE PEMBELAJARAN IPA DI MI NEGERI SIKANCO KECAMATAN NUSAWUNGU KABUPATEN CILACAP TAHUN PELAJARAN 2014/2015 - Nasikhotun Nadiroh (IAIN Purwokerto, 2015)
Abstract: The results showed that the activity of leaming science by using more than one kind of leaming makes students feel bored. Teachers applying science teaching methods that include: the preparation phase, the implementation phase and evaluation phase. Preparation is the preparation that every day is to make lesson plans and preparation or consideration before using the method. The implementation stage is the stage of the application of science teaching methods. Evaluation through the assessment phase is to measure the extent to which students are able to absorb the material of science leaming and to assess the effectiveness of the methods used to increase the effectiveness of leaming. Teachers use the test in the fonm of written tests, the practice of direct and oral test. Keywords: method of learning IPA, MI State Sikanco